Origin of the Submillimeter Radio Emission During the Time-Extended Phase of a Solar Flare - Trottet, G. (2011)
Solar flares observed in the 200 - 400 GHz radio domain may exhibit a slowly varying and time-extended component which follows a short (few minutes) impulsive phase and can last for a few tens of minutes to more than one hour. The few examples discussed in the literature indicate that such long-lasting submillimeter emission is most likely thermal bremsstrahlung. We present a detailed analysis of the time-extended phase of the 27 October 2003 (M6.7) flare, combining 1 - 345 GHz total-flux radio measurements with X-ray, EUV, and Hα observations. We find that the time-extended radio emission is, as expected, radiated by thermal bremsstrahlung. Up to 230 GHz, it is entirely produced in the corona by hot and cool materials at 7 - 16 MK and 1 - 3 MK, respectively. At 345 GHz, there is an additional contribution from chromospheric material at a few 104 K. These results, which may also apply to other millimeter-submillimeter radio events, are not consistent with the expectations from standard semiempirical models of the chromosphere and transition region during flares, which predict observable radio emission from the chromosphere at all frequencies where the corona is transparent.